Rancang Bangun Alat Pembuat Minuman Kawa Daun Otomatis Berbasis Mikrokontroler - chairunnisa nisa; Rahmi Eka Putri (Universitas Andalas, 2022)
This research was conducted with the aim of making it easier for people to enjoy kawa daun drinks automatically, without using human intervention in the manufacturing process. Currently, the process of making kawa daun drinks still uses the manual method, namely by boiling dried and roasted coffee leaves, the dosing of each component and the use of hot water for this drink are still different depending on the maker. Therefore we need a system that can facilitate the community in making this kawa leaf drink, namely by measuring the components of the drink using a weight sensor. For the use of hot water in the manufacture of this drink, hot water with a temperature of 80-90 OC is used, which will be measured using the DS18b20 temperature sensor. This tool is designed using Arduino Mega 2560, Weight sensor, DS18b20 temperature sensor, servo motor, DC motor, HX711 module, relay, mini water pump, keypad, and LCD.